Assessing vulnerability to climate variability and change: participatory assessment approach and Kenyan case study - Isabel van de Sand (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Although the need for adaptation to climate variability and change is increasingly recognized, identifying and implementing adaptation options on the ground still presents a challenge. Especially for Africa, which is regarded as being particularly vulnerable to the impacts of climate variability and change, identifying viable adaptation strategies that can be implemented at the community level are of critical importance. This study uses participatory approaches to assess vulnerability to climate variability and change and to identify adaptation options for a watershed in Kenya, which presents a critical water resource for the city of Nairobi. Participatory approaches have been applied in the development community for years through the use of participatory rural appraisal techniques and have recently also been advocated in the context of adaptation to climate change. The application of participatory approaches for the purpose of this study allowed identifying key constraints in adaptive capacity and ways on how to overcome these together with the affected communities.
Keywords: 330; Armut und Ungleichheit; Klimawandel; Landwirtschaft und ländliche Entwicklung; Umwelt; Ökosysteme und Ressourcen; Wasser; Klimawandel; Wirtschaftliche Anpassung; Wasserversorgung; Partizipation; Kenia; Nairobi